On the Complex Oscillation of Meromorphic Solutions of Nonhomogeneous Linear Differential Equations with Meromorphic Coefficients. (9th November 2020) - Chen, Chuang-Xin; Cui, Ning; Chen, Zong-Xuan
Abstract : In this paper, we study the higher order differential equation f k + B f = H, where B is a rational function, having a pole at ∞ of order n > 0, and H ≡ 0 is a meromorphic function with finite order, and obtain some properties related to the order and zeros of its meromorphic solutions.